2021
DOI: 10.1101/2021.09.16.460709
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metabolic diversity and aero-tolerance in anammox bacteria from geochemically distinct aquifers

Abstract: Background: Anaerobic ammonium oxidation (anammox) is important for converting bioavailable nitrogen into dinitrogen gas, particularly in carbon poor environments. Yet, the diversity and prevalence of anammox bacteria in the terrestrial subsurface – a typically oligotrophic environment – is little understood across different geochemical conditions. To determine the distribution and activity of anammox bacteria across a range of aquifer lithologies and physicochemistries, we analysed 16S rRNA genes, metagenomes… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 113 publications
(161 reference statements)
0
3
0
Order By: Relevance
“…While recent studies have suggested that anammox bacteria are most likely oxygen tolerant rather than strictly anaerobic 53,54 , the comparatively high abundance of anammox in the attached phase could also be due to anaerobic zones deeper in the biofilm. Further, transcriptional activity of anammox genes associated with Brocadia were found in aquifers with anoxic-to-oxic conditions suggesting anammox bacteria are able to contribute to nitrogen loss in a diverse range of oxygen environments 55 .…”
Section: Resultsmentioning
confidence: 99%
“…While recent studies have suggested that anammox bacteria are most likely oxygen tolerant rather than strictly anaerobic 53,54 , the comparatively high abundance of anammox in the attached phase could also be due to anaerobic zones deeper in the biofilm. Further, transcriptional activity of anammox genes associated with Brocadia were found in aquifers with anoxic-to-oxic conditions suggesting anammox bacteria are able to contribute to nitrogen loss in a diverse range of oxygen environments 55 .…”
Section: Resultsmentioning
confidence: 99%
“…Research into anammox located in deep sea anoxic nitrate-ammonium transition zones observed expression of full gene sets for flagella mobility despite limited energy for mobility, suggesting flagellar activity is linked to in situ growth 72 . Similarly, other Planctomycetes bacteria have shown increased flagella mobility in highly rich media 73 suggesting AMX may utilize chemotaxis within high nutrient concentrations as opposed to mobility to avoid oxygen stress 74 .…”
Section: Resultsmentioning
confidence: 99%
“…Studies that reported abundances found that organisms of this candidate phylum always constituted <1% of the community. Currently, there is only one Hydrogenedentota MAG available from Shark Bay (Skoog et al, 2022), but MAGs of Hydrogenedentota have been assembled from other environments including subsurface waters (Momper et al, 2018;Mosley et al, 2022;Tully et al, 2018), hot spring water and sediments (Liew et al, 2022;Zhou et al, 2020), marine sediment (Zhou, Mara, et al, 2022), freshwater sediment (Hahn et al, 2022;Jaffe et al, 2023), hydrothermal vents (Speth et al, 2021;Zhong et al, 2022;Zhou, St. John, et al, 2022), anaerobic digesters and annamox bioreactors (Campanaro et al, 2020;Lin et al, 2021;Nobu et al, 2015;Pabst et al, 2022;Rinke et al, 2013;Suarez et al, 2022;Wang et al, 2020;Wang et al, 2022;Zhang et al, 2022), wastewater (Grégoire et al, 2023;Haryono et al, 2022;Huang et al, 2021;Parks et al, 2017) and saline and hypersaline sediments (Uzun et al, 2020;Vavourakis et al, 2019). Of these studies, only one characterized this organism and identified Ca.…”
Section: Introductionmentioning
confidence: 99%